Is 'Genocide' an Anachronistic Concept for the Study of Early Modern Mass Killing? - Kiernan, Ben (History, 2014)
Is it anachronistic to apply the term 'genocide', coined in 1943, to ancient or early modern mass killings, even to those that might fit the mid-twentieth- century definition? Historians must analyse actions and events of the pre-modern era in the context of cultural stipulations discussed at the time, and of knowledge paradigms then available. To assess people's actions by standards understood in that era, it is important to determine whether a pre-modern understanding of the concept of genocide existed. Long before that term, earlier terms such as 'general massacre' conveyed similar meanings, along with four much older, related terms - holocaust, extermination, crimes against humanity, and war crimes - which also conveyed pre-modern concepts of the crimes involved. This essay traces the historical lineage and usage of those terms in European and transnational contexts, and argues that conceptions of genocide long pre-dated the coining of the term. Genocide did occur in early modern times, though it was neither normal practice nor universally permitted and often provoked dissent. The essay concludes that a grasp of the concept and its moral implications long preceded both our word for it and its 1950 legal codification as an international crime. The essay then critiques common misunderstandings of that legal definition: that it refers to the crime's effect rather than the perpetrator's intent; that it is too broad for historians to use; that only a state can commit genocide; that it must involve the participation of an entire ethnic group; and that it must be complete, not partial.